ANALISIS KEPEMIMPINAN, BUDAYA ORGANISASI DAN KOMPENSASI TERHADAP KINERJA KARYAWAN MELALUI LOYALITAS KARYAWAN PADA PT. SYNERGY FIRST LOGISTICS YOGYAKARTA - Jemiyanto, Dodik Dwi (UPAJIWA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2018)
The research was conducted to test leadership variable influence, organization culture, and compensation of the performance of them through loyality to PT. Synergy first Logistics yogyakarta. Sampling technique used simple random sampling. The sample Is employee of Synergy combat yogyakarta which consisted of 41 peoples. The collection of data using koesioner. The analysis used is technique analysis spss 16.0 path by the tools. And smartpls 3.0. Based on analysis of the data and the results of the testing of hypotheses to research can be concluded that leadership have a negative influence on loyalty employees. Culture organization have had a positive impact of loyalty employees. Compensation have had a positive impact of loyalty employees. Leadership have had a positive impact on the performance of employees. Culture organization have a negative influence on of employee performance. Compensation have a negative influence on loyalty employees. Loyalty have had a positive impact on the performance of an employee. Simultaneously variable leadership, organization culture , and compensation had a positive impact on loyalty. Simultaneously variable leadership, organization culture, compensation and positive impact on the performance with loyalty.   Keywords: Discipline, Communication, Leadership, Motivation, commitment